2020
DOI: 10.2298/bah2004487m
|View full text |Cite
|
Sign up to set email alerts
|

Technical and economic performance of dairy cattle farming in mountain areas in Tizi-Ouzou, Algeria

Abstract: The aim of this study is to explore the technical and economic aspects of cattle farms in mountain areas and to identify their technical constraints and potentialities. One hundred dairy cattle farmers were surveyed for seven months. The results show that the average farm size is 13 dairy cows and shows considerable variability at the sample level. For one-third of the farms, stabling is almost permanent and feed concentrate used as supplement (on average 7 kg /cow/day). 85% of the factors of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
0
7
2
Order By: Relevance
“…The level of education of breeders is often very low; 39.4% of breeders are unlettered, and 34.9% have a primary education level. Low literacy is a concept often observed in rural areas of Algeria, and it's partly explained by the farms location in remote areas without schools and cultural centers (Benidir et al, 2020;Mouhous et al, 2020).…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%
“…The level of education of breeders is often very low; 39.4% of breeders are unlettered, and 34.9% have a primary education level. Low literacy is a concept often observed in rural areas of Algeria, and it's partly explained by the farms location in remote areas without schools and cultural centers (Benidir et al, 2020;Mouhous et al, 2020).…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%
“…An attention-grabbing figure in the current study is the relatively high illiteracy rate, especially in Algeria (39%) and Tunisia (44%). Low literacy is a concept often observed in rural areas in Algeria and Tunisia, and it is partly explained by the farms' location in remote areas, without schools and cultural centers [18,19]. Even in Greece, where 80% of farmers have completed the basic education, only a very small percentage (5%) indicated that they have received some kind of training related to animal breeding.…”
Section: Farmers' Socio-economic Identificationmentioning
confidence: 99%
“…In Tunisia and Algeria, more than 70% of the surveyed farmers opt for this profession due to heritage, while in Greece, the principal reason for this choice is the love for the profession (49%). Profit as a reason for practicing the profession varied throughout the three countries: 28% in Greece, 30% in Algeria, and only 5% in Tunisia, which was probably due to the limited productive performances of the indigenous cattle breeds (Chi-square = 275.687; df (18); p < 0.01; Cramer's V = 0.600) (Figure 1).…”
Section: Farmers' Socio-economic Identificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Resonance in terms of milk chain helps to improve the capacity of producers, in order to solve difficulties, make production decisions and exploit loopholes through the interventions of all key players in the chain (SOLTANI, 2017). Dairy production development policies should focus on strategies to improve productivity and profitability in mountainous areas (Mouhous, Djellal, Guermah, & Kadi, 2020). Small-scale milk producers have become key players in all channels.…”
Section: Introductionmentioning
confidence: 99%